The Effect of Developmental Mindset and Innovative Work Behavior on Performance Moderated by Workplace Happiness at PT Elnusa Construction Fabrication - Yura, Irvianty; Pasaribu, Bomer; Samosir, Partogi Saoloan (Krisnadwipayana International Journal of Management Studies, 2025)
This study aims to determine the effect of a growth mindset and innovative work behavior on performance with happiness at work as a moderating variable at PT Elnusa Fabrikasi Konstruksi. The sample used in this study were 84 employees who worked at PT Elnusa Fabrikasi Konstruksi using a questionnaire to collect data. The sampling technique used a simple random sample. The data analysis technique uses SEM PLS to measure the outer model, inner model and moderation variable analysis which results in convergent validity, discriminant validity, composite reliability & conbach alpha and hypothesis testing. The results showed that the variables of growth mindset, innovative work behavior and happiness in the workplace had a significant effect on the performance variable, the variable of growth mindset moderated by happiness at work had no effect on performance and the variable of innovative work behavior moderated by happiness at work had no effect on employee performance.